A longitudinal microbiological investigation of Actinobacillus actinomycetemcomitans and Eikenella corrodens in juvenile periodontitis. - Mandell, R L (1984)
Longitudinal clinical and microbiological monitoring of subjects with localized juvenile periodontitis indicated that Actinobacillus actinomycetemcomitans and Eikenella corrodens were significantly associated (P less than 0.05) with active tissue destruction.